Profit-Shifting Elasticities, Channels, and the Role of Tax Havens: Evidence from Micro-Level Data - Valeria Merlo; Georg Wamser (Center for Economic Studies and ifo Institute (CESifo), 2024)
This chapter reviews the literature providing empirical estimates on the tax elasticity of multinational profits and discusses the challenges faced when attempting to quantify tax-motivated profit shifting. We first use micro-level data to show that multinational corporations hold a disproportionately large share of profits and financial assets in tax havens, relative to real activities in these countries. We then argue that tax notches associated with anti-tax avoidance legislation may be exploited to better understand tax-motivated profit shifting. This approach suggests a semi-tax elasticity of pre-tax profits of about 0.22, which is substantially smaller than estimates provided in earlier studies.
Keywords: H25; H26; 330; corporate income taxes; profit shifting; tax havens; multinational corporations